Manifestations of hard and soft technologies in immersive spaces - Dron, J.; Reiners, Torsten; Gregory, S. (EdITLib, 2011)
Immersive spaces are innately flexible. However, for learners, some constraints and scaffolding may often be valuable. This paper looks at immersive spaces as soft and hard technologies. Soft technologies are technologies enabling creative and flexible use, while hard technologies embed processes that limit creativity but provide efficiency and freedom from error. Technologies may be softened or hardened by assembly. For instance, if your Learning Management System (LMS) has no wiki, then it may be softened by adding one from outside the system. If your wiki has no assessment management system, then it may be hardened by using a LMS. For learning, the intrinsically soft nature of immersive spaces sometimes requires scaffolded hardening. This paper provides an example of an ongoing project that realizes these soft and hard technologies in an immersive virtual space and discusses the rich potential of such spaces for technology assembly.